2017
DOI: 10.1007/s13311-017-0546-7
|View full text |Cite|
|
Sign up to set email alerts
|

Chronic Paroxetine Treatment Prevents the Emergence of Abnormal Electroencephalogram Oscillations in Huntington's Disease Mice

Abstract: Disturbance of rapid eye movement (REM) sleep appears early in both patients with Huntington’s disease (HD) and mouse models of HD. Selective serotonin reuptake inhibitors are widely prescribed for patients with HD, and are also known to suppress REM sleep in healthy subjects. To test whether selective serotonin reuptake inhibitors can correct abnormal REM sleep and sleep-dependent brain oscillations in HD mice, we treated wild-type and symptomatic R6/2 mice acutely with vehicle and paroxetine (5, 10, and 20 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 57 publications
2
11
0
Order By: Relevance
“…The total amount of non–rapid eye movement (NREM) and rapid eye movement (REM) sleep over 24 h as well as homeostatic responses to sleep loss were not affected by the mutation (Fisher et al, 2016). In the R6/2 model, these HD-evoked changes in the EEG responded to treatment with either a serotonin uptake inhibitor (paroxetine; Kantor et al, 2017) or a hypnotic (zolpidem; Kantor et al, 2016). The circuits responsible for REM and NREM sleep are centered in the basal forebrain, lateral hypothalamus, and brainstem (Weber and Dan, 2016; Saper and Fuller, 2017; Scammell et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The total amount of non–rapid eye movement (NREM) and rapid eye movement (REM) sleep over 24 h as well as homeostatic responses to sleep loss were not affected by the mutation (Fisher et al, 2016). In the R6/2 model, these HD-evoked changes in the EEG responded to treatment with either a serotonin uptake inhibitor (paroxetine; Kantor et al, 2017) or a hypnotic (zolpidem; Kantor et al, 2016). The circuits responsible for REM and NREM sleep are centered in the basal forebrain, lateral hypothalamus, and brainstem (Weber and Dan, 2016; Saper and Fuller, 2017; Scammell et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The administration of the Orx receptors antagonist during the inactive behavioral period of R6/1 mice was associated with the attenuation of the power of the beta activity and the restoration of the sleep-wake cycle to some extent. Significantly, other studies have reported that a single administration of hypnotic drugs acting on the GABAergic or noradrenergic systems, or anti-depressant substances, also decreases the amplitude of the beta/gamma activity in R6/2 mice [51,52], while such data are not available in the R6/ 1 model. However, hypnotic drugs also affect other physiological brain waves that are not associated with HD pathology, such as theta activity expressed typically during REM sleep by increasing theta power and decreasing its frequency both in rodents [53] and humans [54].…”
Section: Discussionmentioning
confidence: 93%
“…This suggests that correcting abnormalities in the 5-HT system stabilized cortical circuits in R6/2 mice (Kantor et al, 2017). Here we found that when chronic paroxetine was started at a presymptomatic age, it allowed MASCO-driven rhythms to be induced at a time when they are not normally inducible in R6/2 mice.…”
Section: Discussionmentioning
confidence: 97%